FOOD PHOTOGRAPHY AS A PROMOTIONAL MEDIA IN INCREASING THE SALES VALUE OF MSME PRODUCTS - sari, winda widya; Putri, Intan; Dendi, Dendi; Mulyadi, Ahmad Iman (Universitas Sang Bumi Ruwa Jurai, 2024)
The community has a role related to national development, especially in building the economic order, namely in establishing micro, small and medium enterprises (MSMEs). The aim of the research is to find out implementation Food Photography as a Promotional Media in increasing the selling value of Pekon Suka Maju MSME products, Kec. Ngaras, Kab. West Coast, Prov. Lampung. This research method uses descriptive qualitative. This research was carried out in Pekon Suka Maju sub-district. Ngaras district. West Coast of Lampung. This research used 2 data collection techniques, namely: Interviews, Interview techniques and Observation. The research results show that Pekon Sukamaju MSMEs previously did not know about product photography techniques, and some of them thought that product photos were not that important for their business, on average consumers found out about their products by word of mouth. However, after they were introduced to product photos and explained that product photos were very important in their business, especially now in the digital era, product photos are the most important thing for introducing MSME products to consumers. Food photography or also known as Food Photography and commercial ads. This product photo can increase the selling value of the product, this is because product photos are the main thing that every MSME must have in order to increase consumer appeal.